Kecerdasan emosi, dukungan sosial, dan perilaku non suicidal self-injury (NSSI) pada mahasiswa baru fakultas kedokteran - Batrisya Aida Agnazahra; Warih Andan Puspitosari (Holistik Jurnal Kesehatan, 2026)
Background: Non-suicidal self-injury (NSSI) is the act of intentionally harming oneself without suicidal intent. New medical students are in the transitional phase of young adulthood, vulnerable to stress. Therefore, protective factors such as social support and emotional intelligence are thought to play a role in NSSI. Purpose: To analyze the relationship between emotional intelligence and social support and the incidence of NSSI in new medical students. Method: This quantitative analytical study, with a cross-sectional design, was conducted among 150 new medical students at the Faculty of Medicine, Universitas Muhammadiyah Yogyakarta (November 2024–June 2025) and recruited using a convenience sampling technique. NSSI was measured using the Inventory of Statements About Self-Injury (ISAS), social support using the Multidimensional Scale of Perceived Social Support (MSPSS), and emotional intelligence using the Bar-on Emotional Quotient Inventory (EQ-i). Relationships were analyzed using the chi-square test, and further analysis within the NSSI group used Spearman correlation. Results: Forty-five respondents (30.0%) reported a history of self-injury (NSSI). The most common form of NSSI was pinching (18.9% of total acts). The highest NSSI functions were self-punishment (mean 1.64) and emotion regulation (mean 1.59). There was no significant relationship between emotional intelligence and NSSI (p=0.299). There was a significant relationship between social support and NSSI (p=0.035), with a tendency for NSSI to be higher in those with low social support. Among respondents with NSSI, total social support was negatively correlated with several NSSI functions, specifically self-punishment, emotion regulation, and family and friend support, which were also negatively correlated with NSSI scores. Conclusion: Social support was significantly associated with NSSI, while emotional intelligence did not show a significant relationship in this study sample. Suggestion: Future research could consider other variables influencing NSSI. A qualitative approach could provide a more in-depth understanding of NSSI behavior.   Keywords: Emotional Intelligence; Freshmen; Non-Suicidal Self-Injury (NSSI) Behavior; Social Support.   Pendahuluan: Non-Suicidal Self-Injury (NSSI) adalah perilaku melukai diri secara sengaja tanpa niat bunuh diri. Mahasiswa baru kedokteran berada pada fase transisi dewasa muda yang rentan stres, sehingga faktor protektif seperti dukungan sosial dan kecerdasan emosional diduga berperan terhadap NSSI. Tujuan: Untuk menganalisis hubungan kecerdasan emosional dan dukungan sosial dengan kejadian NSSI pada mahasiswa baru. Metode: Penelitian kuantitatif analitik dengan desain cross-sectional, dilakukan pada 150 mahasiswa baru Fakultas Kedokteran Universitas Muhammadiyah Yogyakarta (November 2024–Juni 2025) yang dikumpulkan menggunakan teknik convenience sampling. NSSI diukur menggunakan inventory of statements about self-injury (ISAS), dukungan sosial dengan multidimensional scale of perceived social support (MSPSS), dan kecerdasan emosional dengan bar-on emotional quotient inventory (EQ-i). Analisis hubungan menggunakan uji chi-square, analisis lanjutan pada kelompok NSSI menggunakan korelasi Spearman. Hasil: Berdasarkan 45 responden (30.0%) melaporkan riwayat NSSI. Bentuk NSSI yang paling sering adalah mencubit (18.9% dari total tindakan). Fungsi NSSI tertinggi adalah self-punishment (rerata 1.64) dan affect regulation (rerata 1.59). Tidak terdapat hubungan bermakna antara kecerdasan emosional dan NSSI (p=0.299). Terdapat hubungan bermakna antara dukungan sosial dan NSSI (p=0.035), dengan kecenderungan NSSI lebih tinggi pada dukungan sosial rendah. Pada responden dengan NSSI, dukungan sosial total berkorelasi negative dengan beberapa fungsi NSSI, terutama self-punishment, affect regulation, dukungan keluarga, dan teman juga berkorelasi negatif dengan skor NSSI. Simpulan: Dukungan sosial berhubungan signifikan dengan kejadian NSSI, sedangkan kecerdasan emosi tidak menunjukkan hubungan yang bermakna pada sampel penelitian ini. Saran: Penelitian selanjutnya dapat mempertimbangkan variabel lain yang memengaruhi kejadian NSSI. Pendekatan kualitatif dapat memberikan pemahaman yang lebih mendalam terhadap perilaku NSSI yang dilakukan.   Kata Kunci: Dukungan Sosial; Kecerdasan Emosional; Mahasiswa Baru; Perilaku Non-Suicidal Self-Injury (NSSI).